Industrial Automatic Assembly Technology Based on Machine Vision Recognition - Xiang, Shiqian (Manufacturing Technology Journal, 2021)
With the rapid development of science and technology, the means of industrial production have become more diversified and intelligent, and the development of new means of industrial production has become an increasingly important research topic. Therefore, the automatic assembly technology was studied taking machine vision system as the main research subject in this study. An automated assembly model of industrial technology based on machine vision recognition was established, parameters such as the part positioning parameter, assembly time, the number of parts wrongly assembled and the number of parts missing and the qualification rate of assembly were obtained, and the corresponding experimental conclusions were obtained. Moreover it was compared with the traditional manual assembly technology, and it was found that the automatic assembly technology based on machine vision recognition had better performance and more remarkable experimental results compared with the traditional manual assembly technology, and the traditional manual assembly technology needed continuous modification and optimization. This work provides a new route for automatic assembly technology in industrial technology.
Keywords: Machine vision; Recognition; Industrial technology; Automated assembly